Foreword - O.H. Muller (AOSIS, 1979)
This year is Health Year. It is also the YEAR OF THE CHILD. There is nothing in life which gives so much pleasure as observing the infant and the child - the physical growth, the development of the intellect and personality, the discovery of a world of its own. There is also hardly anything that affects one so deeply and exacts so much compassion as interference with this generally accepted process of development.